Study on Optimal Operation for Concentrating Solar Power Plants Considering Wind Power Reduction. Issue 5 (July 2020) - Yuan, Guochun; Guo, Panfeng
Abstract: Concentrating solar power (CSP) generation units, which can generate electricity without any pollutant emissions, is one of the most attractive alternatives to fossil fuels. However, the main disadvantage of the CSP device is the high investment cost. In order to improve the economic feasibility, it is necessary to properly design the thermal energy storage (TES) device to optimize its economic benefits. In this paper, considering the operation requirements of power system, the optimal co-allocation model of solar energy field and TES device is established to weigh the investment cost and wind power reduction. Through a case study, the effectiveness of using energy storage to improve wind power consumption is verified on the basis of considering the constraints of the actual operation of the system, solar radiation and wind energy uncertainty.